IDENTITIES IN EFL CREATIVE WRITING IN INDONESIA - Dewi Widyastuti; Khin Khin Aye; Melinda Kong; Carolyn Beasley; Novita Dewi (Sanata Dharma University, 2021)
Creative writing is created for aesthetic rather than informative purposes and its creation is greatly influenced by the writers’ background. Thus, how the writers’ perception of themselves or their identities are expressed in the creative writing products. As such, creative writing in the English as a foreign language (EFL) context may offer a space for foreign language learners to express their perceived identities. In this study, an analysis of two short stories written by students of the English Letters Department, Universitas Sanata Dharma, Yogyakarta, Indonesia, revealed that the students’ perceived identities were used as the resources for their creative writing outputs. In the first short story entitled “Calling Him Back”, through the internal conflicts of the main character, the student writer expressed her doubt as to which identities to claim. In the second short story entitled “Happy Birthday”, the student writer exploits her identities as a literature student when she did a research on novels with Indian background. The data were gathered through document analysis on the two short stories and correspondences with the student writers. These two short stories were evidence that foreign language learners utilized different aspects of their multifaceted identities as the resources for their creative writing outputs.